The United Nations at fifty: adjusting the multilateralism system (segunda de dos partes) - Andy Knight, W. (CIENCIA ergo-sum; Vol. 4 Núm. 1 (1997): CIENCIA ergo-sum (marzo-junio 1997), 2017)
This paper is a brief examination of the adjustment which the UN system has been undergoing in an attempt to remain a relevant actor on the multilateral stage. The discussion of the processing of adjusting the UN multilateral system to a changing global environment is done within the context of the major UN reform proposals and positions that have coined the political debate among the primary actors involved in the reform process.